Juridical Analysis Of The Existence Of Land Bank On The Law About Work Creation - Hidayanti, Elvi; Listiyani, Nurul (International Journal of Educational Research & Social Sciences, 2023)
In 2020, Law Number 11 of 2020 concerning Job Creation was introduced. From this Job Creation Act, a new agency was born, namely the Land Bank Agency, which is a special institution that manages land. Whereas previously there was a National Land Agency in charge of land affairs. With the existence of two institutions that regulate the same thing, it is feared that there will be overlapping powers. After the issuance of the Job Creation Act, in April 2021 the government issued a derivative rule Number 64 of 2021 concerning the Land Bank Agency. However, in November 2021 it turned out that the Constitutional Court issued Decision Number 91/PUU-XVIII/2020. However, despite the issuance of Decision Number 91/PUU-XVIII/2020, the president still issues presidential decrees, namely presidential regulation number 113 of 2021 concerning The Structure and Administration of The Land Bank. This is contrary to the previous decision of the constitutional court. The purpose of this study is to determine the indications of equal authority between the Land Bank Agency and the National Land Agency and how the existence of the Land Bank Agency after the Constitutional Court Decision Number 91/PUU-XVIII/2020 This research uses normative research or commonly referred to as library research. This research approach uses a law approach, a conceptual approach and a philosophical approach.Indications of the same authority between the Land Bank Agency and the National Land Agency are Land Procurement and Land Utilization Control, for the Land Bank Agency itself to obtain Management Rights so that the difference in the task area between the two institutions is visible. However, with the issuance of Presidential Decree Number 113 of 2021, it is a violation and the existence of the Land Bank Agency can be null and void by law.